Perigos da leitura no feminino. Dos livros proibidos aos aconselhados (séculos XIX e XX) - Irene Vaquinhas (Ler História, 2010)
The Author covers the evolution of the authorized and recommended reading for women, as well as the prohibited reading over a significant part of the nineteenth and twentieth centuries. The dynamisms found are pointed out as well as the continuities in both the Constitutional Monarchy in the First Republic, and eventually in the Estado Novo. Regardless of the involving political regime, the Author notes the continuing condemnation of the sentimental novels, outlining, however, dynamics and significant differences in terms of principles and practices.